Behavior Systems Learning Model on Prayer Material at SMP Muhammadiyah 8 Batu - Romelah Romelah; Anizak Umilatifah; Zakiyah Zakiyah (Universitas Muhammadiyah Malang, 2024)
This research aims to describe the impact of presenting prayer material to class VII students at SMP Muhammadiyah 8 Batu and the implementation of teaching prayer material using a behavioural system model. This approach uses qualitative research with a case study type; the informants are one teacher and 12 students, and one boy and one girl are taken from each class. Data collection techniques include interviews, observation, and documentation. Data analysis uses the model from Miles, Huberman and Saldana through four activities that co-occur: data collection, data reduction, data presentation and conclusion drawing or verification. The results of this research show that (1) The impact of the prayer material presented to class VII students on the element of knowledge, with indicators that informants are accustomed to praying five times a day according to the time, the importance of praying and the reasons for leaving it, and when they are busy they still pray. The element of memorizing or reading prayers, from takbiratul ihram to greetings. (2) Implementation of learning prayer material using a behavioural system model for class VII students in 3 steps; first, the teacher has planned by making a lesson plan for prayer material whose reference is in the Muhammadiyah HPT book. Second, the implementation of learning begins with the teacher opening the lesson, presenting prayer material by reading and memorizing prayer readings, starting from takbiratul ihram, Iftita', ruku', I'tidal, prostration, sitting between two prostrations, initial and final tasyahud and greetings. The methods used are lecture, memorization, drill, reward and punishment—learning strategies with peer teaching (peer teaching). Third, the teacher conducts evaluations every class hour, inviting students to read and memorize prayer readings together. If you read and memorize incorrectly, the teacher immediately reminds you, corrects and repeats the reading or memorization.